A case report of knee meniscal tear due to combat sports injuries - Masitha, Siti; Fatmarizka, Tiara; Abdurrasyid, Abdurrasyid (Universitas Muhammadiyah Magelang, 2023)
A knee meniscus tear is a sports injury that commonly occurs due to sudden twisting movements. This condition causes various levels of musculoskeletal pain. This case report aimed to evaluate exercise therapy to reduce pain in patients with lateral meniscus tears. We presented a 26 years old female patient diagnosed with a lateral, medial meniscus tear and left lateral meniscus tear due to a combat sports injury. Physiotherapy interventions were given in ice packs, Transcutaneous Electrical Nerve Stimulation (TENS), and Ultrasound (US) to reduce pain. Our study concluded that physiotherapeutic intervention reduced the pain due to the integument rupture and vice versa, increasing the range of motion and thigh muscle strength. Keywords: Pain management; case report; physiotherapy; healthcare professionals; innovation in musculoskeletal care